Unmasking gender disparities in cocoa farming: the case of female land ownership in the Ashanti and western north regions of Ghana - Buabeng, K.; Lohr, K.; Asare, R.; Sieber, S. (2024)
Ghana's economy relies heavily on agriculture, with subsistence farming being the primary source of income for rural households. Over 50% of the food grown worldwide is produced by women. Land ownership is paramount to be recognized as a cocoa farmer in Ghana, as most land is owned by men following traditional inheritance. This gives men access to, and control over, land for agriculture, thus creating structural gender inequalities. Thereby, women's contribution to agriculture is minimized and roles undermined. This study analyses the challenges faced by women cocoa farmers in the context of land ownership and how they are influenced by social and demographic factors. We focus on ownership including sole ownership. The study, conducted in seven communities across the Ashanti and Western North regions of Ghana, comprises 160 females and 40 males. Results indicate that ownership of cocoa plots, in general, is mostly male dominated, but when female farmers make farmland decisions, they are likely to be sole owners. Marital status and the mode of acquiring lands are very important factors that dictate ownership and sole ownership of land. While the results show the importance of land as a resource that can enhance women's agricultural productivity, it also highlights that policies to reduce gender inequality in agriculture by advancing land rights are needed.